2012
DOI: 10.1007/s11096-012-9678-3
|View full text |Cite
|
Sign up to set email alerts
|

Validation of pharmacogenetic algorithms and warfarin dosing table in Egyptian patients

Abstract: Our study showed that genotype-based dosing improved prediction of warfarin therapeutic dose beyond that available with the fixed-dose approach or the clinical algorithms, especially in the low-dose group. However, the two pharmacogenetic algorithms were the most accurate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 30 publications
3
17
2
1
Order By: Relevance
“…We demonstrated that the Gage genetic algorithm predicted the largest proportion of patients within ideal dose (65%) followed by IWPC algorithm (58%), warfarin label (37%), Gage clinical algorithm (37%), and IWPC clinical algorithm (36%). This is in agreement with those reported by Finkelman et al [25] and in discordance with Bazan et al [13] in which the warfarin dosing table predicted the largest proportion of patients within ideal dose (28.6), followed by the Gage genetic algorithm (27%), the IWPC genetic algorithm (25.4%), the Gage clinical algorithm (23.8), and the IWPC clinical algorithm (22.4%). In this study, the genetic algorithms predicted warfarin dose in only 25% of patients for the Gage genetic algorithm and 32% for the IWPC genetic algorithm.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…We demonstrated that the Gage genetic algorithm predicted the largest proportion of patients within ideal dose (65%) followed by IWPC algorithm (58%), warfarin label (37%), Gage clinical algorithm (37%), and IWPC clinical algorithm (36%). This is in agreement with those reported by Finkelman et al [25] and in discordance with Bazan et al [13] in which the warfarin dosing table predicted the largest proportion of patients within ideal dose (28.6), followed by the Gage genetic algorithm (27%), the IWPC genetic algorithm (25.4%), the Gage clinical algorithm (23.8), and the IWPC clinical algorithm (22.4%). In this study, the genetic algorithms predicted warfarin dose in only 25% of patients for the Gage genetic algorithm and 32% for the IWPC genetic algorithm.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, the genetic algorithms predicted warfarin dose in only 25% of patients for the Gage genetic algorithm and 32% for the IWPC genetic algorithm. These results are in agreement with Roper et al [26] and in discordance with Bazan et al [13] in which the Gage and IWPC genetic algorithms predicted a warfarin dose in 57.1% of their cohort of Egyptian patients. The discordance of our data from that reported by Bazan et al [13] could be attributed to the larger sample size and strict exclusion criteria in our study and more percentage of patients in their study taking warfarin ≥7 mg/day (44.4 vs. 30% in the current study).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…To our knowledge, there were no warfarin pharmacogenomic studies carried in Egypt, with the exception of only three studies [26,27,30] in the preceding 2 years. The novel attribute of our study was the development of a warfarin dosing algorithm based on the genetic and nongenetic factors of the study cohort, and the validation of the calculated warfarin dosing algorithm in a different cohort with a significant positive correlation observed between the predicted warfarin dose and the actual prescribed dose.…”
Section: Discussionmentioning
confidence: 99%
“…Un ejemplo de ello fue la menor exactitud de predicción del algoritmo del IWPC en una muestra de pacientes egipcios (16). Incluso en grupos étnicos como los han de China, ha sido necesario incluir otras variables predictoras como el gen CYP4F2 (17).…”
unclassified